2018
DOI: 10.1007/s10936-018-9579-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessing False-Belief Understanding in Children with Autism Using a Computer Application: A Pilot Study

Abstract: We have developed a False-Belief (FB) understanding task for use on a computer tablet, trying to assess FB understanding in a less social way. It is based on classical FB protocols, and additionally includes a manipulation of language in an attempt to explore the facilitating effect of linguistic support during FB processing. Specifically, the FB task was presented in three auditory conditions: narrative, silent, and interference. The task was assumed to shed new light on the FB difficulties often observed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 60 publications
1
7
0
Order By: Relevance
“…Our results suggest that children with ASD can understand others' false beliefs when cognitive demands are sufficiently reduced, but their false-belief processing unfolds more slowly than in TD children. Our findings are thus broadly consistent with recent evidence demonstrating that task demands impact false-belief performance (Rubio-Fernández and Geurts, 2013;Chevallier et al, 2014;Setoh et al, 2016;Carlsson et al, 2018;Bialecka-Pikul et al, 2019;Psouni et al, 2019;Salter and Breheny, 2019;Scott et al, 2020). More generally, this study offers a promising new paradigm exploring social cognitive processing in children with ASD.…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that children with ASD can understand others' false beliefs when cognitive demands are sufficiently reduced, but their false-belief processing unfolds more slowly than in TD children. Our findings are thus broadly consistent with recent evidence demonstrating that task demands impact false-belief performance (Rubio-Fernández and Geurts, 2013;Chevallier et al, 2014;Setoh et al, 2016;Carlsson et al, 2018;Bialecka-Pikul et al, 2019;Psouni et al, 2019;Salter and Breheny, 2019;Scott et al, 2020). More generally, this study offers a promising new paradigm exploring social cognitive processing in children with ASD.…”
Section: Discussionsupporting
confidence: 92%
“…Studies demonstrated high levels of heterogeneity across tasks used to assess diagnostic discriminative ability, the type of technology used to implement them, primary metrics evaluated and developmental domains assessed. Tasks were presented on portable technologies, such as laptops ( H. Li & Leung, 2020 ; Lu et al, 2019 ), tablet computers ( Anzulewicz et al, 2016 ; Bovery et al, 2021 ; Campbell et al, 2019 ; Carlsson et al, 2018 ; Carpenter et al, 2021 ; Chen et al, 2019 ; Chetcuti et al, 2019 ; Dawson et al, 2018 ; Fleury et al, 2013 ; Gale et al, 2019 ; Jones et al, 2018 ; Mahmoudi-Nejad et al, 2017 ; Ruta et al, 2017 ), smartphones ( Mahmoudi-Nejad et al, 2017 ; Rafique et al, 2019 ; Zhao & Lu, 2020 ), intelligent toys ( Moradi et al, 2017 ) and digital audio recorders ( Nakai et al, 2014 ; Wijesinghe et al, 2019 ), and non-portable technologies, such as desktop computers ( Aresti-Bartolome et al, 2015 ; Borsos & Gyori, 2017 ; Chaminade et al, 2015 ; Crippa et al, 2013 ; Deschamps et al, 2014 ; Dowd et al, 2012 ; Gardiner et al, 2017 ; Gyori et al, 2018 ; Hetzroni et al, 2019 ; J. Li et al, 2020 ; P. Li et al, 2016 ; Lin et al, 2013 ; Martin et al, 2018 ; Veenstra et al, 2012 ) and VR platforms of varying sophistication ( Jung et al, 2006 ; Jyoti & Lahiri, 2020 ; Alcañiz Raya et al, 2020 ;…”
Section: Resultsmentioning
confidence: 99%
“…In total, 21 studies (55.3%) used gamified tasks ( Anzulewicz et al, 2016 ; Aresti-Bartolome et al, 2015 ; Carlsson et al, 2018 ; Chaminade et al, 2015 ; Chen et al, 2019 ; Chetcuti et al, 2019 ; Crippa et al, 2013 ; Deschamps et al, 2014 ; Dowd et al, 2012 ; Fleury et al, 2013 ; Gale et al, 2019 ; Gardiner et al, 2017 ; Hetzroni et al, 2019 ; Jones et al, 2018 ; P. Li et al, 2016 ; H. Li & Leung, 2020 ; Lu et al, 2019 ; Mahmoudi-Nejad et al, 2017 ; Rafique et al, 2019 ; Ruta et al, 2017 ; Veenstra et al, 2012 ), making these the most common type of performance-based tasks to detect autism risk in early childhood. Other types of assessments included video recording of children’s behaviours while they viewed or interacted with stimuli presented on a screen ( n = 9; 23.7%) ( Borsos & Gyori, 2017 ; Bovery et al, 2021 ; Campbell et al, 2019 ; Carpenter et al, 2021 ; Dawson et al, 2018 ; Gyori et al, 2018 ; J. Li et al, 2020 ; Martin et al, 2018 ; Zhao & Lu, 2020 ), tasks using VR platforms ( n = 4; 10.5%) ( Jung et al, 2006 ; Jyoti & Lahiri, 2020 ; Alcañiz Raya et al, 2020 ; Shahab et al, 2017 ) and audio recording of children’s speech ( n = 2; 5.2%) ( Nakai et al, 2014 ; Wijesinghe et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this might seem relatively uncomplicated in this example, in the context of a series of actions and mental state inferences, keeping track of who knows what and when might become quite complex. Some patients with neurological, psychiatric, or developmental disorders such as autism show significant impairments on such false belief tasks [29], and may therefore be particularly vulnerable during natural social interactions which require to identify and engage in appropriate social sequences.…”
Section: Early Work On Social Sequencingmentioning
confidence: 99%